PELATIHAN PEMBUATAN KERIPIK IKAN GABUS (Channa striata) DI KAMPUNG YOBOI, SENTANI, JAYAPURA - Mishbach, Imam; Gea, Liyatin; Tuhumena, Lolita; Ohee, Henderite L.; Runtuboi, Dirk Y. P. (Pattimura University, 2024)
The Wali Nibhi Reading House Group, also known as the Yoboi Reading House, was established in November 2019 in Yoboi Village, Sentani, Papua, with a focus on literacy improvement and women's empowerment. The group is predominantly composed of women, making it well-suited to develop skills in producing snakehead fish chips. However, they still face challenges in terms of skills and facilities. The existing skills are not yet sufficient to process fish into value-added products. The community's high dependence on the fisheries sector makes the local economy vulnerable to fluctuations in catch and environmental impacts. Training on processing snakehead fish into low-calorie chips through baking could address these issues. The method used is community-based training. Training in the production of fish stick chips and atom crackers has provided the community with new knowledge and skills. This program is crucial for local economic empowerment, teaching processing techniques and entrepreneurial skills that can increase income and well-being. The training utilizes local natural resources and strengthens the community's self-reliance and competitiveness in a broader market.